POLITIK PENINGKATAN KEKAYAAN: Negara dan Peranannya dalam Mengentaskan Kemiskinan - Nur, Isnayati (ASAS, 2013)
Abstrak: The problem of poverty became a necessity faced by many countries including Indonesia. Several solutions have been implemented by the government, but only a temporary solution so it does not run in the long term. The main problem of poverty caused by the unequal wealth distribution so that the natural resources that exist only enjoyed by the majority party, while by not enjoyed by the other party. In fact the capitalist economic system can not provide a solution to the problems faced by the country. Islamic economic system felt able to overcome these problems is to set up a mechanism so that the distribution of wealth is not only accumulate wealth on the part alone. Key word : Poverty, distribution, Islamic economic system